ANALISIS IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ETAP DAN SYARIAH PADA KOPERASI JASA KEUANGAN SYARIAH KOMUNITAS USAHA MIKRO MUAMALAT BERBASIS MASJID DARUSSALAM PEMALI - Nadilah Intan Amni; Muh. Misdar; Rizki Rizki (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
The research aims to determine the suitability of the financial statements of the Sharia Financial Services Cooperative Of The Muamalat Micro Enterprise Community Based on The Darussalam Pemali Mosque based on the prevailing Entities Without Public Accountability and Sharia Financial Accounting Standards. The type of research is qualitative descriptive. This research was conducted at the Sharia Financial Services Cooperative of The Muamalat Micro Enterprise Community Based on The Darussalam Pemali Mosque. Data collection techniques consist of observation, documentation and interviews. While data analysis techniques consist of data collection, data reduction, data presentation and conclusion drawing. The results of this study show that the financial statements of KJKS KUM3 Darussalam Pemali have not been fully in accordance with the prevailing Sharia ETAP Financial Accounting Standards. This is indicated by the absence of a comparison of the two periods in the presentation of financial statements, not yet appropriate in compiling the balance sheet report, profit and loss, changes in equity, cash flow and has not made a report on zakat funds, welfare funds and notes on financial statements. Factors of discrepancy in the application occur due to lack of Human Resources, the attachment of the system to the center, lack of understanding by practitioners and lack of attention from the government or cooperative agencies related to the development of sharia cooperatives.